Monitoring vaginal electrical impedance in crossbred cows during post-partum period - Malakar, Subrota; Juyena, Nasrin Sultana; Paul, Sattwikesh; Hasan, Mohammad Mahmudul; Bhattacharjee, Jayonta; Mollah, Habibur Rahman; Islam, Mohammad Rashedul (Asian Journal of Medical and Biological Research, 2017)
Efficient and accurate detection of estrus and correct time of artificial insemination are essential for sustainable dairy farms. Therefore, this study was carried out to monitor oestrus by observing vaginal electrical impedance (VEI) in post-partum cows. Eighteen cows with 19-139 post-partum days were included for this study. Daily VEI values were measured with heat detector®. Lower vaginal electrical resistance (VER) values were recorded during oestrus. VER of 210-240 ? might be indicative for oestrus in cows. The day difference between two successive lower values or higher values in VER waves ranged from 18 to 22 days in cows which might indicates the oestrous cycle length. Marked variation existed between VER values of two successive peaks in pregnant and non-pregnant cows, and increased (P < 0.05) VER values were observed in 2nd peak in pregnant cows. VER of 320-370 ? at 19-22 days after AI could be considered for early pregnancy. The study suggests that the measurement of vaginal impedance could serve as an indicator of the oestrus in cows and daily impedance measurements are necessary to confirm the stages of the estrous cycle, correct time of AI and early pregnancy. Asian J. Med. Biol. Res. June 2017, 3(2): 221-225